Current status of pharmacological treatment of symptomatic irreversible pulpitis - Mamani Usecca, Evelyn Mercedes (2022)
In this literature review article, the objective is to present recommendations for the systemic and local pharmacological treatment of symptomatic irreversible pulpitis, which is one of the most frequent causes of visits to the dentist in search of a treatment for pain. According to articles found in databases such as PubMed, Cochrane, Science Direct, Google Scholar, in addition to the 2017 consensus of the European Society of Endodontics (all of them with a high level of scientific evidence), premedication with non-steroidal anti-inflammatory drugs increases the rate of success of local anesthesia providing predictable anesthesia, saline solution as an irrigant at 2.5 °C reduces postoperative pain, the prescription of antibiotics is prohibited in biopulpectomies since it does not reduce postoperative pain and NSAIDs are the drugs of choice for the pain control after root canal treatment.